2021
DOI: 10.3390/cancers13112654
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning Improves Pancreatic Cancer Diagnosis Using RNA-Based Variants

Abstract: For optimal pancreatic cancer treatment, early and accurate diagnosis is vital. Blood-derived biomarkers and genetic predispositions can contribute to early diagnosis, but they often have limited accuracy or applicability. Here, we seek to exploit the synergy between them by combining the biomarker CA19-9 with RNA-based variants. We use deep sequencing and deep learning to improve differentiating pancreatic cancer and chronic pancreatitis. We obtained samples of nucleated cells found in peripheral blood from 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…This is probably due to the complexity of the genetic component of pancreatic cancer, which makes it not easily explainable. It is widely accepted that other low penetrance genes play a role in pancreatic cancer ( Milne et al, 2009 ; Klein and Westenberger, 2012 ; Al-Fatlawi et al, 2021 ). When we looked deeper into biomarker studies, including both pancreatic and ovarian cancer, we realized that both pancreatic and ovarian cancer are similar in terms of tissue structure, and both are located in the endocrine system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is probably due to the complexity of the genetic component of pancreatic cancer, which makes it not easily explainable. It is widely accepted that other low penetrance genes play a role in pancreatic cancer ( Milne et al, 2009 ; Klein and Westenberger, 2012 ; Al-Fatlawi et al, 2021 ). When we looked deeper into biomarker studies, including both pancreatic and ovarian cancer, we realized that both pancreatic and ovarian cancer are similar in terms of tissue structure, and both are located in the endocrine system.…”
Section: Discussionmentioning
confidence: 99%
“…Identifying highly accurate biomarkers is a complex problem. CA19-9, for example, is well established in pancreatic cancer but has only an accuracy of 70–80% ( Al-Fatlawi et al, 2021 ), which means that it is not suitable for diagnosis on its own, but only to monitor relapse after surgery. One way to improve accuracy and robustness of the diagnoses is to employ biomarker signatures instead of only using single biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Al-Fatlawi et al demonstrated that in conjunction with Ca 19-9, RNA-based variants can be utilized to differentiate between resectable PC, non-resectable PC, and chronic pancreatitis through DL with an AUC of 0.9. Additionally, their neural network was able to identify two mutations, B4GALT5 and GSDMD, which are closely related to PC progression and survival [26]. With the addition of genomic variants, not only can we diagnose PC at an earlier stage, but we can potentially offer patients a more personalized treatment regimen and prognostication as novel targeted therapeutic options are developed.…”
Section: Applications In the Diagnosis Of Pancreatic Ductal Adenocarc...mentioning
confidence: 99%
“…The convolutional neural network (CNN) is a branch of deep learning which was successfully applied in the image analysis such as the detection, classi cation, segmentation, and prediction tasks using medical image data such as pathology, X-ray, CT and MRI. The medical images are also quite a promising eld of research by using CNN in the detection and classi cation of pathology and the prediction of clinically relevant outcomes [15][16][17][18][19][20][21][22][23][24][25][26] . In our knowledge, there have been no reports of deep learning using CNN in the analysis of DWI and prognosis of lung cancer.…”
Section: Introductionmentioning
confidence: 99%